Aplicação de modelagem hidrológica associada à análise geoespacial, para caracterização da vazão na micro Central Hidroelétrica Ilha Anchieta - SP - Bignotto, Rafael Beltrame [UNESP] (2014)
The increasing demand for energy oriented for sustainable resources, stimulates the implementation and development of micro hydropower plants. Because the lack of hydrological information, the implementation or expansion projects, usually carry uncertainties about the technical, economic and environmental feasibility of the project, bringing doubts about the true remaining hydropower potential. The lack of observational data complicates the decision making by the analyst. Recently, advances in geographic information systems - GIS have created many opportunities for improving hydrological models capable of simulating these variables on watershed systems. The ability to perform spatial analyzes for the development of concentrated and distributed hydrological parameters not only saves time and effort, but also improves the accuracy over traditional methods. In this sense, the objective of this work is the application of a hydrological model associated with geospatial analysis in the basin of micro hydropower plant Anchieta Island, for evaluation of hydropower potential. Topographic maps and data from the rain gauge stations were used for interpolation, and estimated numbers in places devoid of information within a GIS environment were used. Although the rainfall monitoring stations disability, interpolation of existing data enabled the characterization the precipitation regime in places devoid of information. The use of HEC- GeoHMS allowed determination of the physical parameters of the basin topographic extracted from the vectorized to be used in the water model HEC- HMS. In the application of hydrological rainfall-runoff model HEC - HMS, the generation of synthetic series of flow allowed to know the highest and lowest flow, and characterize the seasonality, supporting the management and planning of actions in the micro hydropower plant